Monitoramento da qualidade da água da bacia hidrográfica do Rio Ligeiro no município de Pato Branco - PR - Luz, Ezequias da (2018)
The objective of this study it was to monitor water quality and to evaluate the self-depuration capacity of hydrographic basin of the Ligeiro River, from the one of its sources until the confluence with the Chopim River. It was established six monitoring points (PM01 to PM06) along of the route. Samples collecting were realized in the different seasons of the year 2017, and they were sent to the laboratory for analysis of the following parameters: temperature, turbidity, total solids, potential of hydrogen (pH), oxygen biochemical demand (BOD), dissolved oxygen (DO), total nitrogen, total phosphorus and thermotolerant coliforms. In addition, the hydraulic-hydrological measurements were performed in all PMs. Based on the results of the laboratory analyses, they were compared with the quality standards established by National Council of Environment (CONAMA, in Portuguese) nº 357/2005, also being calculated the Water Quality Index (WQI) and done the calibration of the QUAL-UFMG, namely the model that was used to evaluate the self-depuration capacity. The monitoring of water quality indicated that some parameters, principally the BOD, don't meet to the conditions and quality standards established by CONAMA Resolution nº 357/2005 in almost all the river course. Based on the WQI, the highest levels of quality were observed in the summer and autumn season, being framed at an optimum level. Therefore, the WQI is related to the flow conditions, considering that the lower quality levels were found in the campaigns related to the low and high rainfall. In relation to the modelling of water quality in the winter season, it was one that presented the highest degree of quality deterioration, with low levels of DO and high concentration of BOD, mainly in the stretch located after the urban perimeter and of point release of effluents, indicating that, in the period of drought, the dilution capacity of water is reduced in relation to the effluent discharges. It concludes that the Ligeiro River is deteriorated from its source, and that its self-depuration capacity presents critical conditions in the period of lower flow. That way, preventive and corrective measures must be implemented in the control of water quality.